Promoting School Events of Triam Wittaya School in Thailand Using Highlight Videos on Facebook - Giatri -; Sabreeyah Doloh (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2024)
This job training report contains the internship conducted at Triam Wittaya School from January 1st to March 7th, 2024. Triam Wittaya School is a secondary school located in Sakho Tai, Mayo, Pattani, Thailand. The author chose Triam Wittaya School for the internship after successfully passing the selection process for an overseas internship program. The main goals of this internship were to teach English to the students at Triam Wittaya School and to create highlight videos for promoting the school, in line with their marketing needs. This was particularly important because most of the school's existing promotional videos were either livestreams or a collage of photos made into video. The methods used during the internship included observation, interview documentation, and editing. The author started by observing the school's Facebook page, then conducted interviews with the internship supervisor about upcoming events. Throughout the internship, the author documented various activities, identifying key areas to record, and deepening the author's understanding of observation and interview techniques. The editing process involved choosing the right visual content, like video clips and photos, and selecting back song music that fit the atmosphere of each event. The author used all these methods to create promotional videos. The result was cinematic recap videos, each about three minutes long, set to music. These videos were then uploaded to the school's Facebook page, with the hope of boosting the school's marketing efforts. The author faced some challenges during the internship, mainly culture shock due to the language differences and the rare use of English. However, the author managed to overcome these obstacles by learning some basics of the local language, using body language to communicate, and asking the supervisor for translation when needed.